Accumulation of heavy metals in the vegetative organs of poplars under their joint introduction to the soil - Оleksandr Danylchuk; Vitalii Gryshko; Lyudmyla Boyko; Nataliia Danylchuk (Біологічні студії)
Background. Studies of plant autecology under excessive heavy metal intake require a thorough understanding of the specifics of the uptake and accumulation of these substances by plants. It is therefore important to study the redistribution of heavy metals in the soil–plant system. Poplars, due to their rapid growth, large assimilative organ surface area, etc., are a suitable object for studying their autecological properties and potential use in the creation of green spaces. Materials and methods. The objects of the study were two-year-old poplar seedlings: ’I-45/51’, ’Lvivska’, ’Robusta’, ’Tronco’, and the soils on which they grow. The plants were watered once a week for 2 months with a mixture of heavy metal compounds at 1, 5, and 10 maximum permissible concentrations (MPC). Mixtures of the following salts were used as heavy metal sources CdSO4, Ni(NO3)2, CuSO4, ZnSO4, Pb(CH3COO)2. The control plants were not exposed to heavy metals. All plants were grown under natural light and temperature. The content of mobile forms of Cu, Zn, Ni, Pb, and Cd in ammonium acetic acid extract from soil was determined and their accumulation in leaves and roots was measured by conventional methods using a C-115PK atomic absorption spectrophotometer Selmi (Ukraine). Statistical processing of the results was carried out using Microsoft Excel 2013. To assess the probability of the difference between the statistical characteristics of two alternative data sets, a univariate analysis of variance using IBM SPSS Statistics 27, ANOVA, was performed. Results. The accumulation and translocation of heavy metals in the soil–plant system was studied in model experiments. The study revealed the peculiarities of heavy metal accumulation in the soils where poplars grew. It was shown that the introduction of heavy metal compounds leads to an increase in the content of mobile forms of the studied elements in the soil. Under the influence of 1, 5, and 10 MPC of heavy metal ions, all cultivars accumulated them more actively in the root system than in the leaves. Conclusions. The studied poplars can be divided into two groups. The first one includes the cultivars ’I-45/51’ and ’Lvivska’ with a high level of heavy metal accumulation and the highest enrichment factor. The second group – ’Tronco’ and ’Robusta’ – includes those with low levels of heavy metal accumulation and low enrichment factors. The results suggest that the poplars of the second group have physiological mechanisms that determine the observed peculiarities of heavy metal translocation.